Historiography of national intellectualism (to the 100th anniversary of the Belarusian State University) - Liahchylin, Anatoly A.; Vorobyova, Svetlana V. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article presents the historiography of intellectualism in the perspective of achievements in the field of logic and national philosophy at Belarusian State University. The first part of the article traces the historiography of logical knowledge from its origins to the present, the second – the historiography of the research of Belarusian State University scientists in the field of national philosophy. Historiography is accompanied by a detailed bibliography, which allows, firstly, to trace the dynamics and filiation of logical and philosophical ideas in the intellectual national history, and secondly, to determine the role and significance of the philosophical community of Belarusian State University in the process of the formation of Belarusian.
Keywords: logic at Belarusian State University; national philosophy at Belarusian State University; I. N. Lushchitsky scientific school; department of history of philosophy and logic; department of philosophy of culture; intellectual history of Belarus